2008
DOI: 10.1086/587158
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Identification of an Ancient Supernova Using Light Echoes in the Large Magellanic Cloud

Abstract: We report the successful identification of the type of the supernova (SN) responsible for the supernova remnant SNR 0509À675 in the Large Magellanic Cloud ( LMC) using Gemini spectra of surrounding light echoes. The ability to classify outbursts associated with centuries-old remnants provides a new window into several aspects of SN research and is likely to be successful in providing new constraints on additional LMC SNe, as well as their historical counterparts in the Milky Way ( MW ). The combined spectrum o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 61 publications
4
93
0
Order By: Relevance
“…This is unlike the youngest known type Ia SNR in the LMC, 0509-67.5, which was according to the light echo spectrum of the supernova an exceptionally bright type Ia (Rest et al 2008), similar to SN 1991T.…”
Section: The Chemical Composition Of Snr 0519-690mentioning
confidence: 62%
“…This is unlike the youngest known type Ia SNR in the LMC, 0509-67.5, which was according to the light echo spectrum of the supernova an exceptionally bright type Ia (Rest et al 2008), similar to SN 1991T.…”
Section: The Chemical Composition Of Snr 0519-690mentioning
confidence: 62%
“…The most secured typing methods are the study of SN optical light echoes (Rest et al 2005(Rest et al , 2008; infrared light echoes can be used to probe the ISM dust, see e.g. Vogt et al 2012), the measurement of the nucleosynthesis products in the ejecta (e.g.…”
Section: The Typing Of Snrs In Generalmentioning
confidence: 99%
“…The identification of GCD explosions with SNe 91T is challenged from observations of the supernova remnant SNR 0509-67.5 in the LMC. First, based on light echo spectra, Rest et al (2008) demonstrated clearly that this SN was a 1991T-like explosion. Second, Schaefer & Pagnotta (2012) ruled out the existence of a companion star in this SNR to very deep limits and thereby argued for a double-degenerate progenitor, which would exclude the canonical single-degenerate formation channel as a path to the GCD model.…”
Section: Introductionmentioning
confidence: 98%